Fracture-resistant flame-retardant data cable and preparation method thereof
By using a flame-retardant outer cover composed of soft wire braided layer and high-density polyethylene in the data cable, the problem of insufficient flexural and flame retardant performance of the data cable is solved, and higher flexural strength, tear resistance and flame retardant effect are achieved.
Patent Information
- Application Number
- CN202510400430.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing data cables have shortcomings in their flexural resistance and flame retardant properties, which leads to prone to breaking during bending and promoting fire during fire, posing safety hazards.
The flexural flame retardant data cable is used composed of a conductor, an insulating layer, a flexural reinforcement layer and a flame retardant outer shield. The flexural reinforcement layer is a rhombus mesh structure with a rhombus-shaped mesh structure. The flame retardant outer shield is coated with a flame retardant outer shield mixture composed of high-density polyethylene, ethylene-vinyl acetate copolymer, magnesium hydroxide, aluminum hydroxide and active nanomagnesium carbonate.
It improves the anti-fracture and fracture performance of the cable, and significantly enhances the flame retardant effect, reduces the amount of smoke during combustion, and improves the thermal stability and fire resistance of the cable material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of cable technology, and in particular to a bend-resistant flame-retardant data cable and a preparation method thereof. Background Art
[0002] With the rapid development of information technology, the use of data cables in various electronic devices has increased significantly. While there are a wide variety of data cables on the market, their flexural strength and flame retardancy still need improvement. Inadequate flexural strength can easily lead to cable breakage during bending, affecting data transmission stability; while poor flame retardancy can fuel a fire, posing a safety hazard.
[0003] Currently, methods for improving the flex resistance of data cables primarily include increasing the thickness of the cable's outer sheath or using more flexible materials. Improving flame retardancy is typically achieved by adding flame retardants to the cable material. However, adding too much flame-retardant filler can negatively impact other cable properties, making it difficult to achieve a balanced balance of flex resistance and flame retardancy, thus failing to meet the high-performance and safety demands of cables in complex operating environments. Summary of the Invention
[0004] In order to improve the problem of poor bending resistance and flame retardancy of data cables, the present application provides a bending-resistant and flame-retardant data cable and a preparation method thereof.
[0005] In a first aspect, the present application provides a bend-resistant flame-retardant data cable, which adopts the following technical solution: A flexure-resistant flame-retardant data cable comprises, from the inside out, a conductor, an insulation layer, a flexure-resistant reinforcement layer, and a flame-retardant outer sheath. The flexure-resistant reinforcement layer is a soft steel wire braided layer having a diamond mesh structure. The flame-retardant outer sheath is formed by coating a flame-retardant outer sheath mixture on the surface of the flexure-resistant reinforcement layer. The flame-retardant outer sheath mixture comprises the following raw materials in parts by weight: 80-100 parts of high-density polyethylene, 15-25 parts of ethylene-vinyl acetate copolymer, 10-20 parts of magnesium hydroxide, 10-15 parts of aluminum hydroxide, and 5-15 parts of active nano-magnesium carbonate.
[0006] By adopting this technical solution, a soft steel wire braid is used as the flexural reinforcement layer, improving the cable's flexural and fracture resistance. The flexural reinforcement layer presents a diamond-shaped mesh, which allows the flame-retardant outer sheath mixture to be firmly adsorbed on the mesh surface and interior of the flexural reinforcement layer, tightly connecting the flame-retardant outer sheath and the flexural reinforcement layer. This results in a compact cable material structure with excellent flexural strength, tear resistance, and flame retardancy.
[0007] In the flame-retardant outer sheath mixture, magnesium hydroxide and aluminum hydroxide serve as inorganic flame retardants. They decompose water vapor and refractory metal oxides at high temperatures, absorbing significant amounts of heat, thereby inhibiting flame spread and improving the cable's flame retardancy. Active nano-magnesium carbonate exhibits excellent smoke-reducing properties, reducing the amount of smoke generated during combustion, lowering its concentration and toxicity. Furthermore, it synergizes with magnesium hydroxide and aluminum hydroxide, forming a dense protective film on the cable material during decomposition, isolating oxygen and inhibiting combustion, improving the cable's thermal stability and enhancing its flame retardancy. High-density polyethylene and ethylene-vinyl acetate copolymer exhibit excellent thermal stability, flexibility, and mechanical strength, enhancing the cable's heat resistance and flexural strength. The addition of ethylene-vinyl acetate copolymer to the flame-retardant outer sheath mixture enhances the integration of magnesium hydroxide, aluminum hydroxide, and active nano-magnesium carbonate with the matrix resin, promoting the dispersion of the flame-retardant particles within the matrix resin, alleviating the problem of particle agglomeration, and improving the uniformity and stability of the cable's flame retardancy. Ethylene-vinyl acetate copolymer can become a physical cross-linking point in the flame-retardant outer sheath mixture, promote the formation of an inorganic network structure between the flame-retardant particles and the matrix, reduce the entanglement of the polymer matrix, and improve the toughness, flexural resistance and strength of the cable material.
[0008] Preferably, the insulating layer comprises the following raw materials in parts by weight: 70-90 parts of methyl vinyl silicone rubber, 15-25 parts of EPDM rubber, 10-15 parts of glass fiber, 3-5 parts of coupling agent, 10-20 parts of activated composite powder, 3-5 parts of aromatic oil, and 1-3 parts of compatibilizer.
[0009] By adopting this technical solution, methyl vinyl silicone rubber and EPDM rubber possess excellent elasticity and thermal stability, maintaining good insulation properties in high-temperature environments, enhancing the tensile strength of the insulation layer, and improving the cable material's flexural resistance. Glass fiber improves the insulation layer's tensile strength and tear resistance, making the cable less susceptible to damage when stretched or bent, and reducing cracking in the cable material.
[0010] Preferably, the activated composite powder is at least two of mica, glass powder, zinc boride and ferrous chloride.
[0011] By adopting this technical solution, mica, glass powder, zinc boride, and ferrous chloride possess excellent high-temperature resistance. When the insulation layer is exposed to high temperatures, the activated composite powder acts as a support, reducing volume shrinkage and preventing cable cracking. The coupling agent promotes the introduction of reactive groups onto the surface of the activated composite powder, increasing the number of active crosslinking points on the surface and enhancing its compatibility with the insulation matrix, thereby improving the tensile and tear strength of the insulation layer.
[0012] Preferably, the compatibilizer is at least one of 4-vinylbenzyl glycidyl ether and 2-phenyl-1,2-pentanediamine.
[0013] By adopting the above technical solution, 4-vinylbenzyl glycidyl ether and 2-phenyl-1,2-pentanediamine can enhance the compatibility between methyl vinyl silicone rubber and EPDM rubber, and can also enhance the crosslinking density and compatibility of the insulation layer material system, thereby improving the tensile strength and tear resistance of the cable material, reducing the phenomenon of cable cracking, and ensuring the long-term safety and smooth operation of the cable.
[0014] Preferably, fireproof mud is pre-coated between the flame-retardant outer protective layer and the anti-flexural reinforcement layer.
[0015] By adopting the above-mentioned technical solution, fireproof mud is coated between the flame-retardant outer sheath and the anti-flexural reinforcement layer, which can effectively prevent flames from spreading inward from the flame-retardant outer sheath. The fireproof mud can fill the gap between the flame-retardant outer sheath and the anti-flexural reinforcement layer, isolating oxygen, preventing the penetration of flames and smoke, and improving the overall fire resistance of the cable. The addition of fireproof mud can extend the fire resistance of the cable under fire conditions. The amount of smoke produced by fireproof mud during combustion is low, which helps to reduce the visibility reduction during fire, improve the safety of personnel evacuation, and buy more time for personnel evacuation and fire fighting. At the same time, compared with conventional flame-retardant materials, fireproof mud has better flexibility and elasticity, which can enhance the cable's anti-flexural performance when bent and reduce cable damage caused by bending of the cable material.
[0016] Preferably, the fireproof mud comprises the following raw materials in parts by weight: 10-20 parts of diatomaceous earth, 0.5-1.5 parts of graphite, 5-10 parts of nano-silicon dioxide, 3-5 parts of methyl cellulose ether, and 5-8 parts of silicate fiber gel.
[0017] By adopting the above technical solution, diatomaceous earth and silicate fiber gel have excellent thermal insulation and fire resistance, which can improve the fire resistance limit and thermal insulation performance of the fireproof mud. Graphite can form graphene layers at high temperatures, further improving the fire resistance of the fireproof mud. Nanosilica has a high specific surface area and dispersibility, which can improve the bonding and sealing properties of the fireproof mud system, allowing the fireproof mud to firmly adhere to the surface of the anti-flexure reinforcement layer and improve the fireproof stability of the cable material. Methyl cellulose ether has excellent film-forming and adhesive properties, which can improve the flexibility and elasticity of the fireproof mud, allowing the fireproof mud to maintain good sealing performance when the cable material is bent and flexed.
[0018] Preferably, the silicate fiber gel is prepared by compounding silicate fiber and silica sol through an infiltration method, and the pore size of the silicate fiber gel is 2-20 nm.
[0019] By adopting the above technical solution, the mesh porous structure of the silicate fiber gel has better isolation and fire prevention performance. At the same time, the porous structure can shorten the drying time of the fireproof mud, improve the drying and cracking prevention effect of the fireproof mud, reduce the cracking and peeling of the fireproof mud, and improve the stability of the fireproof performance of the cable material.
[0020] Preferably, the silicate fiber is one of ceramic fiber and aluminum silicate fiber.
[0021] By adopting the above technical solution, ceramic fibers and aluminum silicate fibers have extremely high heat resistance and chemical stability, can withstand high temperatures up to 1200°C, can effectively prevent the spread of flames, and improve the fire resistance of cable materials.
[0022] In a second aspect, the present application provides a method for preparing a bend-resistant flame-retardant data cable, which adopts the following technical solution: A method for preparing a flexure-resistant flame-retardant data cable comprises the following specific steps: High-density polyethylene, ethylene-vinyl acetate copolymer, magnesium hydroxide, aluminum hydroxide and active nano-magnesium carbonate are mixed and kneaded to form a flame-retardant outer protective mixture; An insulating layer is wrapped around the outer surface of the conductor, and then soft steel wire is woven outside the insulating layer to form a flexural reinforcement layer. A flame-retardant outer sheath mixture is then coated on the outer surface of the flexural reinforcement layer to form a flame-retardant outer sheath, thereby producing a flexural flame-retardant data cable.
[0023] By adopting the above technical solution, the flame-retardant outer sheath mixture is coated on the surface of the anti-flexural reinforcement layer formed by braiding soft steel wire, which can promote the flame-retardant outer sheath material to be firmly bonded with the anti-flexural reinforcement layer, and enable the cable material to have both good anti-flexural strength and flame retardant effect.
[0024] Preferably, methyl vinyl silicone rubber, EPDM rubber, glass fiber, coupling agent, activated composite powder, aromatic oil and compatibilizer are mixed and kneaded to form an insulating layer mixture; Mixing diatomaceous earth, graphite, nano-silica, methyl cellulose ether and silicate fiber gel to form fireproof mud; The insulating layer mixture is wrapped on the outer surface of the conductor to form an insulating layer, and then soft steel wire is woven outside the insulating layer to form a flexural reinforcement layer. A layer of fireproof mud is coated on the outer surface of the flexural reinforcement layer, and then a flame-retardant outer sheath mixture is coated on the outer surface of the fireproof mud to form a flame-retardant outer sheath, thereby producing a flexural and flame-retardant data cable.
[0025] In summary, this application has the following beneficial effects: 1. Because this application utilizes a diamond-shaped mesh of soft steel wire braided as the flexural reinforcement layer, the flame-retardant outer sheath mixture is firmly adsorbed on the mesh surface and interior of the flexural reinforcement layer, resulting in the cable material having excellent flexural strength, impact resistance, and flame retardancy. Furthermore, the use of active nano-magnesium carbonate in the flame-retardant outer sheath mixture synergizes with magnesium hydroxide and aluminum hydroxide, resulting in a better flame retardant effect for the cable material and reducing the amount of smoke generated during combustion.
[0026] 2. In this application, fire retardant mud is pre-coated between the flame-retardant outer sheath and the anti-flexural reinforcement layer. The various components of the fire retardant mud work synergistically to fill the gap between the flame-retardant outer sheath and the anti-flexural reinforcement layer, preventing the penetration of flames and smoke, and improving the overall fire resistance of the cable. The fire retardant mud and the flame retardant protective mixture are used to synergistically enhance the flame retardant and fireproof effects of the cable material. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] All raw materials in the examples are commercially available. Example Example 1
[0029] This embodiment provides a flexure-resistant flame-retardant data cable, which comprises, from the inside out, a conductor, an insulation layer, a flexure-resistant reinforcement layer, and a flame-retardant outer sheath. The conductor is made of copper, the insulation layer is made of methyl vinyl silicone rubber, and the flame-retardant outer sheath mixture comprises the following raw materials by weight: 90 kg of high-density polyethylene, 20 kg of ethylene-vinyl acetate copolymer, 15 kg of magnesium hydroxide, 13 kg of aluminum hydroxide, and 10 kg of active nano-magnesium carbonate. The density of high-density polyethylene is 930 kg / m 3 The content of vinyl acetate in ethylene-vinyl acetate copolymer is 20%, the average particle size of magnesium hydroxide and aluminum hydroxide is 1-5 μm, and the average particle size of active nano-magnesium carbonate is 20-50 nm.
[0030] The preparation method of the flexure-resistant flame-retardant data cable comprises the following specific steps: High-density polyethylene, ethylene-vinyl acetate copolymer, magnesium hydroxide, aluminum hydroxide and active nano-magnesium carbonate are mixed and kneaded at 170° C. to form a flame-retardant outer protective mixture.
[0031] An insulating layer with an average thickness of 0.5-0.8mm is extruded on the surface of the conductor, and then soft steel wire with a diameter of 3.5mm is woven on the outer surface of the insulating layer to form an anti-flexural reinforcement layer with a diamond mesh structure. The flame-retardant outer sheath mixture is then extruded and coated on the outer surface of the anti-flexural reinforcement layer to form a flame-retardant outer sheath with an average thickness of 3-5mm to produce a anti-flexural flame-retardant data cable. Example 2
[0032] The difference between Example 2 and Example 1 is that the amount of high-density polyethylene used in the flame-retardant outer sheath raw material of the bend-resistant flame-retardant data cable is 80 kg, the amount of ethylene-vinyl acetate copolymer used is 25 kg, the amount of magnesium hydroxide used is 10 kg, the amount of aluminum hydroxide used is 15 kg, and the amount of active nano-magnesium carbonate used is 5 kg. Example 3
[0033] The difference between Example 3 and Example 1 is that the amount of high-density polyethylene used in the flame-retardant outer sheath raw material of the bend-resistant flame-retardant data cable is 100 kg, the amount of ethylene-vinyl acetate copolymer used is 15 kg, the amount of magnesium hydroxide used is 20 kg, the amount of aluminum hydroxide used is 10 kg, and the amount of active nano-magnesium carbonate used is 15 kg. Example 4
[0034] Example 4 differs from Example 1 in that the insulation layer of the flexurally resistant flame-retardant data cable comprises the following raw materials in parts by weight: 80 kg of methyl vinyl silicone rubber, 20 kg of EPDM rubber, 13 kg of glass fiber, 4 kg of coupling agent, 15 kg of activated composite powder, 4 kg of aromatic oil, and 2 kg of compatibilizer. The coupling agent is KH-570, the activated composite powder is a mixture of mica and glass powder in a 1:1 mass ratio, and the compatibilizer is 4-vinylbenzyl glycidyl ether.
[0035] The preparation method of the flexure-resistant flame-retardant data cable comprises the following specific steps: High-density polyethylene, ethylene-vinyl acetate copolymer, magnesium hydroxide, aluminum hydroxide and active nano-magnesium carbonate are mixed and kneaded at 170° C. to form a flame-retardant outer protective mixture.
[0036] Methyl vinyl silicone rubber, EPDM rubber, glass fiber, coupling agent, activated composite powder, aromatic oil and compatibilizer are mixed and kneaded at 170° C. to form an insulating layer mixture.
[0037] The insulating layer mixture is extruded and coated on the surface of the conductor to form an insulating layer with an average thickness of 0.5-0.8mm. Then, soft steel wire with a diameter of 3.5mm is woven on the outer surface of the insulating layer to form an anti-flexural reinforcement layer with a diamond mesh structure. Then, the flame-retardant outer sheath mixture is extruded and coated on the outer surface of the anti-flexural reinforcement layer to form a flame-retardant outer sheath with an average thickness of 3-5mm, thereby producing a anti-flexural flame-retardant data cable. Example 5
[0038] The difference between Example 5 and Example 4 is that the amount of methyl vinyl silicone rubber used in the raw materials of the bending-resistant flame-retardant data cable insulation layer is 70 kg, the amount of EPDM rubber used is 25 kg, the amount of glass fiber used is 10 kg, the amount of coupling agent used is 5 kg, the amount of activated composite powder used is 20 kg, the amount of aromatic oil used is 3 kg, and the amount of compatibilizer used is 1 kg. Example 6
[0039] The difference between Example 6 and Example 4 is that the amount of methyl vinyl silicone rubber used in the raw materials of the bending-resistant flame-retardant data cable insulation layer is 90 kg, the amount of EPDM rubber used is 15 kg, the amount of glass fiber used is 15 kg, the amount of coupling agent used is 3 kg, the amount of activated composite powder used is 10 kg, the amount of aromatic oil used is 5 kg, and the amount of compatibilizer used is 3 kg. Example 7
[0040] The difference between Example 7 and Example 4 is that the activated composite powder in the raw material of the bending-resistant flame-retardant data cable insulation layer is a mixture of zinc borate and ferrous chloride, and the mass ratio of zinc borate to ferrous chloride is 1:1. Example 8
[0041] The difference between Example 8 and Example 4 is that the compatibilizer in the raw material of the anti-bend flame-retardant data cable insulation layer is 2-phenyl-1,2-pentanediamine. Example 9
[0042] Example 9 differs from Example 4 in that the flex-resistant flame-retardant data cable is pre-coated with fire-retardant mud between the flame-retardant outer sheath and the flex-resistant reinforcement layer. The fire-retardant mud comprises the following raw materials in parts by weight: 15 kg of diatomaceous earth, 1 kg of graphite, 8 kg of nano-silica, 4 kg of methyl cellulose ether, and 7 kg of silicate fiber gel. The nano-silica has an average particle size of 50-80 nm, and the silicate fiber gel is made of aluminum silicate fibers and silica sol. The aluminum silicate fibers have a diameter of 2 μm and an average length of 20 mm.
[0043] The preparation method of the flexure-resistant flame-retardant data cable comprises the following specific steps: S1: High-density polyethylene, ethylene-vinyl acetate copolymer, magnesium hydroxide, aluminum hydroxide and active nano-magnesium carbonate are mixed and kneaded at 170° C. to form a flame-retardant outer protective mixture.
[0044] S2: Methyl vinyl silicone rubber, EPDM rubber, glass fiber, coupling agent, activated composite powder, aromatic oil and compatibilizer are mixed and kneaded at 170° C. to form an insulating layer mixture.
[0045] S3: Apply uniform pressure to the aluminum silicate fiber to expel the air inside, and gradually infiltrate the silica sol into the aluminum silicate fiber. The mass ratio of aluminum silicate fiber and silica sol is 1:1. Heat to 60°C to generate a silicate fiber gel with an average pore size of 2-20nm; mix diatomaceous earth, graphite, nano-silica, methyl cellulose ether and silicate fiber gel, stir evenly to form a fireproof mud.
[0046] S4: The insulation layer mixture is extruded and coated on the surface of the conductor to form an insulation layer with an average thickness of 0.5-0.8mm, and then soft steel wire is woven on the outer surface of the insulation layer, with a diameter of 3.5mm, to form a flexural reinforcement layer with a diamond mesh structure, and then fireproof mud is coated on the outer surface of the flexural reinforcement layer to form a fireproof mud layer with an average thickness of 2mm, and then the flame-retardant outer sheath mixture is extruded and coated on the outer surface of the fireproof mud to form a flame-retardant outer sheath with an average thickness of 3-5mm, thereby obtaining a flexural and flame-retardant data cable. Example 10
[0047] The difference between Example 10 and Example 9 is that the amount of diatomaceous earth used in the raw materials of the anti-flex flame-retardant data cable fireproof mud is 10 kg, the amount of graphite used is 1.5 kg, the amount of nano-silica used is 10 kg, the amount of methyl cellulose ether used is 5 kg, and the amount of silicate fiber gel used is 8 kg. Example 11
[0048] The difference between Example 11 and Example 9 is that the amount of diatomaceous earth used in the raw materials of the anti-flex flame-retardant data cable fireproof mud is 20 kg, the amount of graphite used is 0.5 kg, the amount of nano-silica used is 5 kg, the amount of methyl cellulose ether used is 3 kg, and the amount of silicate fiber gel used is 5 kg. Example 12
[0049] The difference between Example 12 and Example 9 is that the silicate fiber gel in the raw material of the flexural flame-retardant data cable fireproof mud is made of ceramic fiber and silica sol. The ceramic fiber has a diameter of 3 μm and an average length of 30 mm. Example 13
[0050] The difference between Example 13 and Example 9 is that silicate fiber gel is not used in the raw materials of the flexural-resistant flame-retardant data cable fire retardant mud.
[0051] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no anti-bending reinforcement layer is used in the anti-bending flame-retardant data cable.
[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that ethylene-vinyl acetate copolymer is not used in the flame retardant outer sheath mixture of the bend-resistant flame retardant data cable.
[0053] The following performance tests were performed on the anti-bend flame-retardant data cables provided in Examples 1-13 and Comparative Examples 1-2 of the present application. The specific test results are shown in Table 1.
[0054] 1. Strength test With reference to GB / T528-2009, "Vulcanized rubber or thermoplastic rubber - Determination of tensile stress-strain properties," the tensile strength of the flexural-resistant flame-retardant data cable prepared in this application was tested using a Type IA dumbbell specimen. With reference to GB / T529-2008, "Vulcanized rubber or thermoplastic rubber - Determination of tear strength," the tear strength of the flexural-resistant flame-retardant data cable prepared in this application was tested using Method A.
[0055] 2. Oxygen Index The oxygen index of the flexural flame-retardant data cable prepared in this application was tested with reference to GB / T 2406.2-2009, "Determination of Combustion Behavior of Plastics by Oxygen Index Method - Part 2: Room Temperature Test." The vertical burning rating of the flexural flame-retardant data cable prepared in this application was tested with reference to GB / T 10707-2008, "Determination of Combustion Properties of Rubber."
[0056] Table 1: Performance test results data table
[0057] Performance test results indicate that the flexural-resistant, flame-retardant data cable prepared in this application exhibits excellent tear resistance, flexural strength, and flame retardancy. A comparison of Comparative Examples 1-2 with Example 1 demonstrates that the present application utilizes a flexural reinforcement layer formed by braiding soft steel wire with a diamond-shaped mesh structure, combined with a flame-retardant outer sheath, to produce a cable material with excellent flexural strength, tear resistance, and flame retardancy. Through the synergistic effects of the various components, the resulting flame-retardant outer sheath mixture forms a dense protective film on the cable material surface, isolating it from oxygen, inhibiting combustion, and improving the cable material's flame retardancy.
[0058] By comparing Examples 4-8 with Example 1, it can be seen that in Examples 4-8, the raw materials of the insulation layer in the cables are different from those in Example 1, and the tensile strength and tear resistance of the prepared cables are significantly improved.
[0059] It can be seen from Examples 9-13 that fire retardant mud is pre-coated between the flame retardant outer sheath and the anti-flexural reinforcement layer. From the performance test results, it can be seen that the tensile strength, flame retardant effect and fireproof effect of the cable are all improved. It further illustrates that the fire retardant mud can enhance the tightness of the cable material structure, improve the stability of the tensile strength and flame retardant effect of the cable material, and enhance the fire resistance limit of the cable material. By comparing Example 13 with Example 9, it can be seen that Example 13 does not use silicate fiber gel, which affects the flame retardant performance and tear resistance of the cable. It further illustrates that the porous structure of silicate fiber gel can further isolate flame combustion, while reducing the cracking and peeling of fire retardant mud and improving the stability of the cable material strength.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A flexure-resistant flame-retardant data cable, characterized in that: From the inside to the outside, there are conductor, insulation layer, anti-flexural reinforcement layer and flame-retardant outer sheath. The anti-flexural reinforcement layer is a soft steel wire braided layer, and the soft steel wire braided layer has a diamond mesh structure. The flame-retardant outer sheath is formed by coating a flame-retardant outer sheath mixture on the surface of the anti-flexural reinforcement layer. The flame-retardant outer sheath mixture includes the following raw materials in parts by weight: 80-100 parts of high-density polyethylene, 15-25 parts of ethylene-vinyl acetate copolymer, 10-20 parts of magnesium hydroxide, 10-15 parts of aluminum hydroxide, and 5-15 parts of active nano-magnesium carbonate.
2. The anti-bending flame-retardant data cable according to claim 1, characterized in that: The insulating layer comprises the following raw materials in parts by weight: 70-90 parts of methyl vinyl silicone rubber, 15-25 parts of EPDM rubber, 10-15 parts of glass fiber, 3-5 parts of coupling agent, 10-20 parts of activated composite powder, 3-5 parts of aromatic oil and 1-3 parts of compatibilizer.
3. The anti-bending flame-retardant data cable according to claim 2, characterized in that: The activated composite powder is at least two of mica, glass powder, zinc boride and ferrous chloride.
4. The anti-bending flame-retardant data cable according to claim 2, characterized in that: The compatibilizer is at least one of 4-vinylbenzyl glycidyl ether and 2-phenyl-1,2-pentanediamine.
5. The anti-bending flame-retardant data cable according to claim 1, characterized in that: Fireproof mud is pre-coated between the flame-retardant outer protective layer and the anti-bending reinforcement layer.
6. The anti-bending flame-retardant data cable according to claim 5, characterized in that: The fireproof mud comprises the following raw materials in parts by weight: 10-20 parts of diatomaceous earth, 0.5-1.5 parts of graphite, 5-10 parts of nano silicon dioxide, 3-5 parts of methyl cellulose ether, and 5-8 parts of silicate fiber gel.
7. The anti-bending flame-retardant data cable according to claim 6, characterized in that: The silicate fiber gel is prepared by compounding silicate fiber and silicon dioxide sol through an infiltration method, and the pore size of the silicate fiber gel is 2-20 nm.
8. The bend-resistant flame-retardant data cable according to claim 7, characterized in that: The silicate fiber is one of ceramic fiber and aluminum silicate fiber.
9. A method for preparing a bend-resistant flame-retardant data cable according to any one of claims 1 to 8, characterized in that: The specific steps include: High-density polyethylene, ethylene-vinyl acetate copolymer, magnesium hydroxide, aluminum hydroxide and active nano-magnesium carbonate are mixed and kneaded to form a flame-retardant outer protective mixture; An insulating layer is wrapped around the outer surface of the conductor, and then soft steel wire is woven outside the insulating layer to form a flexural reinforcement layer. A flame-retardant outer sheath mixture is then coated on the outer surface of the flexural reinforcement layer to form a flame-retardant outer sheath, thereby obtaining a flexural flame-retardant data cable.
10. The method for preparing the bend-resistant flame-retardant data cable according to claim 9, characterized in that: Methyl vinyl silicone rubber, EPDM rubber, glass fiber, coupling agent, activated composite powder, aromatic oil and compatibilizer are mixed and kneaded to form an insulating layer mixture; Mixing diatomaceous earth, graphite, nano-silicon dioxide, methyl cellulose ether and silicate fiber gel to form fireproof mud; Wrap the insulating layer mixture on the outer surface of the conductor to form an insulating layer, then weave soft steel wire outside the insulating layer to form a flexural reinforcement layer, apply a layer of fireproof mud on the outer surface of the flexural reinforcement layer, and then apply the flame-retardant outer sheath mixture on the outer surface of the fireproof mud to form a flame-retardant outer sheath to obtain a flexural-resistant flame-retardant data cable.
Citation Information
Patent Citations
Insulation material for silicone rubber composite cable used in nuclear power station
CN102220007A
Flame-retardant power cable
CN106251969A
Low-voltage fireproof cable
CN107545947A
Anti-adhesion low-smoke halogen-free and flame-retardant polyolefin cable material
CN111635580A
Bending-resistant polyvinyl chloride insulation sheath shielding flexible cable
CN210489272U